The Effects of Prebiotic Dietary Fibers, Probiotics, and Synbiotics on Gut Permeability and Immunity: A Systematic Review - Leila Maghsoumi-Norouzabad; Alireza Bagherzadeh-Karimi; Shabnam Aliakbari Majd; Leila Hosseini; Fatemeh Shahi (Iranian Journal of Medical Sciences)
Background: Modulation of intestinal barrier, which function through zonulin pathway downregulation, represents a promising therapeutic strategy for chronic diseases. This systematic review aimed to evaluate the effects of prebiotic dietary fibers, probiotics, and synbiotics on intestinal permeability and immunity. Methods: A systematic literature search of the EMBASE, PubMed, Web of Science, and Scopus electronic databases was conducted from database inception up to May 2024, supplemented by manual reference list searches. Included studies met the following criteria: (a) English language publications; (b) clinical trials; (c) investigated each factor of serum or fecal zonulin levels, serum or fecal calprotectin, glucagon-likepeptide-2 (GLP-2), short chain fatty acids (SCFAs), long chain fatty acids (LCFAs), fecal bile acid (BA), LPS-binding protein (LBP), lipopolysaccharide (LPS), intestinal microbiota composition, or inflammatory factors such as interleukin 6 (IL-6) and high-sensitivity C-reactive protein (hs-CRP); (d) supplemented prebiotic dietary fibers, probiotics, or symbiotics. Studies were excluded if they contained insufficient data or involved supplementation alongside other interventions. The study quality and risk of bias were assessed using Jadad’s Score.Results: A total of 36 studies were included in this review. Of these, 14 articles (n=580 participants) evaluated the effect of dietary prebiotics, 18 articles (n=1502 participants) evaluated the effect of probiotics, and six articles (n=517 participants) examined the effect of synbiotics on intestinal health and immunity markers. According to the evidence presented in this study, prebiotic whole foods or food enriched with prebiotics, probiotics, and synbiotics might have favorable effects on the serum levels of zonulin as a measure of intestinal permeability. The effects on GLP-2, gut microbiota, and their metabolites (e.g., LCFAs/SCFAs and BA) were contradictory and inconclusive. Some studies indicated increased levels of Bifidobacteria and SCFA with prebiotic supplementation or prebiotics-enriched food products. Fecal calprotectin (as an important marker of the local gut inflammation), tumor necrosis factor-α (TNF-α), and hs-CRP were unaffected in most studies. Conclusion: The lack of consistent replication across studies made it difficult to draw definitive conclusions about the effects of prebiotics, probiotics, and synbiotics on gut-related health and immunity. Therefore, further evidence is required before definitive recommendations can be established.